2004
DOI: 10.1002/clc.4960270506
|View full text |Cite
|
Sign up to set email alerts
|

Reduced quality of life after myocardial infarction in women compared with men

Abstract: SummaryBackground: Psychosocial factors have been suggested as risk factors for atherosclerotic disease.Hypothesis: The purpose of the present study was to examine whether there is a gender difference in quality of life after a myocardial infarction with modern treatment of acute ischemic heart disease.Methods: In all, 123 men and women aged between 31 and 80 years, and with a hospital-diagnosed myocardial infarction occurring 1-12 months prior to inclusion, were studied. Minor symptoms evaluation profile (MSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
33
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 20 publications
10
33
1
Order By: Relevance
“…Although some demographic factors, such as female gender and younger age were reported as predictors of low quality of life and psychological recovery in previous studies [24][25][26], we did not find any difference in demographic factors among the three sub-groups. From the medical history, the Weary group had the highest percentage with a history of diabetes, hypertension, and comorbidity, but the percentage of CABG and cardiac rehabilitation referral was not different between the three groups.…”
Section: ) and Based On The Combined Calinski And Harabasz And Duda Andcontrasting
confidence: 82%
“…Although some demographic factors, such as female gender and younger age were reported as predictors of low quality of life and psychological recovery in previous studies [24][25][26], we did not find any difference in demographic factors among the three sub-groups. From the medical history, the Weary group had the highest percentage with a history of diabetes, hypertension, and comorbidity, but the percentage of CABG and cardiac rehabilitation referral was not different between the three groups.…”
Section: ) and Based On The Combined Calinski And Harabasz And Duda Andcontrasting
confidence: 82%
“…Previous studies using various HRQoL measures have consistently found that women with CHD had poorer HRQoL. [25][26][27][28][29] In addition, McCollum et al 29 found that after adjustment for sociodemographic and comorbid factors, women with diabetes had higher self-rated health compared with men with diabetes, despite having similar or poorer HRQoL as measured by the SF-12 MCS and PCS in MEPS. It appears that these paradoxical results suggest some differences between self-rated health and objective health measures.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports confirmed worse QoL in women after MI compared to men of the same age, and although QoL improves with time in both genders, this effect is more pronounced in men [3][4][5]. Some differences have also been noted in relation to QoL dimension, with some studies indicating that the improvement in men mostly involves the physical dimension of QoL [6].…”
Section: Introductionmentioning
confidence: 99%